Aberrant cervical vasculature anastomosis as cause of neck pain and successful treatment with embolization technique. (1st February 2016) - He, Lucy; Ladner, Travis R; Cobb, Mark; Mocco, J
Abstract : We report a patient with non-dermatomal radiating neck pain without focal neurologic deficit. Traditional workup could not identify an anatomic or biomechanical cause. Imaging showed a deep cervical vessel centered in the region of pain. Angiography later identified an aberrant anastomosis of this vessel with the occipital artery. Subsequent endovascular embolization of this arterial trunk resulted in complete pain relief.